2010
DOI: 10.1007/s11270-010-0491-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Changes in Selected Operational Descriptors of Dissolved Organic Matters From Various Sources in a Watershed

Abstract: Microbial changes in selected operational descriptors of dissolved organic matters (DOMs) from nine different sources (treated sewage, algae, soils, sediment, plants), which include a broad spectrum of potential organic precursors in the Han River watershed, were investigated using 28-day microbial incubation experiments. The DOM descriptors investigated were specific UV absorbance, fluorescence index, humification index, synchronous fluorescence spectra, apparent molecular weight (MW), and the extent of pyren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 45 publications
2
19
1
Order By: Relevance
“…In contrast, the DOM sources with very high SUVA values such as CP and LT presented the smaller extent of the decreases (34–38%) upon photodegradation. The more pronounced changes in the SUVA values relative to the DOC concentrations suggest that aromatic chromophores were preferentially removed and a large portion of the oxidized aromatic structures within the DOM may be partially transformed into non UV‐absorbing compounds by irradiation . Chow et al have also shown no significant changes in the DOC concentrations of surface water samples, but found a decrease of SUVA values after photodegradation.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the DOM sources with very high SUVA values such as CP and LT presented the smaller extent of the decreases (34–38%) upon photodegradation. The more pronounced changes in the SUVA values relative to the DOC concentrations suggest that aromatic chromophores were preferentially removed and a large portion of the oxidized aromatic structures within the DOM may be partially transformed into non UV‐absorbing compounds by irradiation . Chow et al have also shown no significant changes in the DOC concentrations of surface water samples, but found a decrease of SUVA values after photodegradation.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, %FLF and % HLF increased with the water level. Synchronous fluorescence spectra of plant-derived DOM are generally characterized by high PLF and low FLF while FLF is predominant for those of soil-derived DOM (Hur 2009). Considering that soil and plant (or forests) leaching are possible mechanisms to provide DOM in rivers during rainfall, our results suggest that the compositional changes in DOM during the storm runoff may be dominated by the inflow of soilderived DOM.…”
Section: Changes In Spectroscopic Characteristicsmentioning
confidence: 99%
“…SUVA values are known to have a positive relationship with aromatic carbon content of DOM (Weishaar et al 2003). In addition, SUVA value may be enhanced by microbial decomposition of DOM and thus higher SUVA value may reflect higher humification, more hydrophobic nature, and lower biodegradability of DOM (Hur 2010). In this respect, the high SUVA value observed at the S1 site appears to be associated with decomposed organic matters from dead algae and vegetation, and terrestrial debris in the sediment near the dam.…”
Section: Resultsmentioning
confidence: 97%